2020
DOI: 10.1111/tbj.14115
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of invasive and in situ breast carcinoma margins in radioactive seed and wire‐guided localization lumpectomies

Abstract: Image‐guided preoperative localizations help surgeons to completely resect nonpalpable breast cancers. The objective of this study is to compare the adequacy of specimen margins for both invasive breast cancer (IBC) and ductal carcinoma in situ (DCIS) after radioactive seed localization (RSL) vs wire‐guided localization (WGL). We retrospectively reviewed 600 cases at a single Canadian academic center from January 2014 to September 2017, comparing surgical margins, re‐excisions and reoperations, localization ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…( p = 0.043) Similar to this finding, the size of DCIS in the postoperative specimen was associated with positive section margins ( p < 0.001). This is comparable to the findings for WGL or radioactive seed localisation [ 19 , 20 , 21 , 22 ]. The determining component for section margins is not solely DCIS, as in 60% of the cases with positive section margins this was due to the invasive component.…”
Section: Discussionsupporting
confidence: 89%
“…( p = 0.043) Similar to this finding, the size of DCIS in the postoperative specimen was associated with positive section margins ( p < 0.001). This is comparable to the findings for WGL or radioactive seed localisation [ 19 , 20 , 21 , 22 ]. The determining component for section margins is not solely DCIS, as in 60% of the cases with positive section margins this was due to the invasive component.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps the use of US and the evaluation of distances from the margins can improve surgeons’ orientation. Law et al reported a re-operation rate of 6% in their study, assessing the adequacy of invasive and in situ breast carcinoma margins in radioactive seed- and wire-guided localization lumpectomies [ 21 ]. Regarding the radiofrequency system, different rates of R0 surgery have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative re-excision rates were reported by 15 studies [31,34,35,40,43,45,50,[62][63][64][65][66]69,70], with a high heterogeneity (I 2 = 95%). The intraoperative re-excision risk in conservative surgery with RSL was higher than with WGL, but this value was not statistically relevant (RR = 1.02, 95% CI = 0.75-1.38; 5623 patients; 15 studies; analysis Figure 7).…”
Section: Intraoperative Re-excisionmentioning
confidence: 99%
“…Reoperation rates were reported by 27 studies [29,35,[38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][57][60][61][62][63][64][65][66][67]69,70], with a relevant heterogeneity (I 2 = 61%). The reoperation risk after conservative surgery with RSL was lower than with WGL (RR = 0.71, 95% CI = 0.61-0.84; 13884 patients; 27 studies; see Figure 8).…”
Section: Reoperationmentioning
confidence: 99%